2023
DOI: 10.1002/adfm.202305383
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Anion‐Capturer with Polymer Chains in Fireproof Gel Polymer Electrolyte Enables Dendrite‐Free Sodium Metal Batteries

Abstract: Sodium metal batteries (SMBs) using gel polymer electrolytes (GPEs) with high theoretical capacity and low production cost are regarded as a promising candidate for high energy‐density batteries. However, the inherent flammability of GPEs and uncontrolled Na dendrite caused by inferior mechanical properties and interfacial stability hinder their practical applications. Herein, an anion‐trapping fireproof composite gel electrolyte (AT‐FCGE) is designed through a chemical grafting–coupling strategy, where functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 58 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…This leads to improved ionic conductivity, accelerated charge transfer kinetics, and enhanced interfacial stability. 348,349…”
Section: Design and Engineering Strategies Of Gpes For Wide-temperatu...mentioning
confidence: 99%
“…This leads to improved ionic conductivity, accelerated charge transfer kinetics, and enhanced interfacial stability. 348,349…”
Section: Design and Engineering Strategies Of Gpes For Wide-temperatu...mentioning
confidence: 99%
“…Last, our DFT results also indicate the affinity of PEO toward h-BN (see Figure S8 in the Supporting Information), which further supports the enhanced nucleation model. Yang et al 33 reported a slightly higher ionic conductivity (×1.5) for BN nanosheet (BNNS)-containing Na gel polymer electrolytes relative to BN-free ones. The improvement in ionic conductivity was attributed to the anion-trapping ability of BNNS and the consequent increase in the free Na + concentration.…”
Section: Ionic Conductivity and Binding Energymentioning
confidence: 99%
“…In the context of energy storage, investigations of structure–property relationships in BN-containing polymer electrolytes for Na-ion conduction are lacking. To the best of our knowledge, only a handful of recent reports have devoted attention to such polymer electrolyte systems. Only one of these reports is based on a CSPE for Na-ion conduction, whereas the remainder of the studies is based on the incorporation of boron into the polymer chain rather than adding a BN-based filler to the polymer matrix. Chen et al , chemically incorporated boron into polymer chains and found a decrease in the total ionic conductivity compared to full-carbon polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bulk polymers are usually thermal insulators, which hinders their capability to dissipate heat in emerging energy intensive applications. Thermal conductivities of bulk polymers are extremely low, on the order of 0.1 W m –1 K –1 , limiting their applications in electronics packaging, , fuel cells, , solar cell, , power batteries, , hydrogen generators, , heat exchangers, and aerospace materials . Polymer chain-aligned films or fibers exhibit a high thermal conductivity on the order of 10–100 W m –1 K –1 , which is close to the intrinsic high thermal conductivity of a well-aligned single polymer chain.…”
Section: Introductionmentioning
confidence: 99%